A modified HLA-A*0201-restricted CTL epitope from human oncoprotein (hPEBP4) induces more efficient antitumor responses. Issue 8 (August 2018) - Sun, Weihong; Shi, Junyi; Wu, Jian; Zhang, Junchu; Chen, Huabiao; Li, Yuanyuan; Liu, Shuxun; Wu, Yanfeng; Tian, Zhigang; Cao, Xuetao; Li, Nan
Abstract We previously identified human phosphatidylethanolamine-binding protein 4 (hPEBP4) as an antiapoptotic protein with increased expression levels in breast, ovarian and prostate cancer cells, but low expression levels in normal tissues, which makes hPEBP4 an attractive target for immunotherapy. Here, we developed hPEBP4-derived immunogenic peptides for inducing antigen-specific cytotoxic T lymphocytes (CTLs) targeting breast cancer. A panel of hPEBP4-derived peptides predicted by peptide-MHC-binding algorithms was evaluated to characterize their HLA-A2.1 affinity and immunogenicity. We identified a novel immunogenic peptide, P40–48 (TLFCQGLEV), that was capable of eliciting specific CTL responses in HLA-A2.1/Kb transgenic mice, as well as in peripheral blood lymphocytes from breast cancer patients. Furthermore, amino-acid substitutions in the P40–48 sequence improved its immunogenicity against hPEBP4, a self-antigen, thus circumventing tolerance. We designed peptide analogs by preferred auxiliary HLA-A*0201 anchor residue replacement, which induced CTLs that were crossreactive to the native peptide. Several analogs were able to stably bind to HLA-A*0201 and elicit specific CTL responses better than the native sequence. Importantly, adoptive transfer of CTLs induced by vaccination with two analogs more effectively inhibited tumor growth than the native peptide. These data indicate that peptide analogs with high immunogenicity represent promising candidates for peptide-mediated therapeutic cancer vaccines.